Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Loyalitas Pelanggan (Universitas Negeri Semarang, 2014)
The objective of the study is to analyze the good effects of product and service quality to the customers loyalty Shop. The population of this study was shop customers Lima Jaya Shop, Pekalongan as much 100 respondents using Proportionate Random Sanpling method. The method used in collecting the data was a questionnaire which was measured by liker scale. Based on the partial test, direct influence of product quality to customer loyalty is 0,020 and direct influence of service quality to customer loyalty is 0,002. This study concludes that there is product quality and service quality are positive and significant partially store customer loyalty. Manajerial implications for the store should have to improve the low dimensional as product durability and conformance of products by providing quality product that include material qualification, theoretical implications of further research are expected to examine other variables such as the belief that it is possible to have a variable effect on customer loyalty.